Web 2.0 Platform As A Creative And Interesting Supplementary Tool For Teaching Writing - Dwita Laksmita Rachmawati; Oikurema Purwati (Jurnal Pendidikan Indonesia, 2021)
In this 21st-century learning, which is interconnected with technological advancements is different from traditional language teaching, means teachers as the agent of education need to promote the rapid penetration of technology into the educational cycle. For that reason, the research examined the English writing teacher's experience in using Facebook, to support EFL learners in a tertiary level education in Indonesia, to know how the teacher integrate social media especially in teaching writing. The participants of the study were 21 EFL learners' majors in the English Department, as well as the instructor of writing class. The data obtained, such as transcript from interviews and class discussion in the platform was analyzed inductively, interpretively and qualitatively. The teacher’s counter-interviews had been tested using initial coding. The research offers language teachers with ideas to be taken into the platform in the context of the EFL and supports better instructional design using Facebook.